Analysis of Students’ Mathematical Reasoning Ability Based on Self-Regulated Learning: A Case Study on Algebraic Expressions - Yantu, Nurul Ainun; Hulukati, Evi; Damayanti, Taulia ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The role of mathematics is not only to emphasize mastery of formulas and calculations, but also to develop students’ mathematical reasoning skills, enabling them to think logically, systematically, and critically in problem-solving. This study aimed to analyze students’ mathematical reasoning skills in terms of self-regulated learning on the topic of algebraic expressions for class VII-B students at SMP Negeri 1 Suwawa. This research employed a descriptive method with a quantitative approach. The sample consisted of 27 students from class VII-B, selected using purposive sampling. The research instruments included a mathematical reasoning skills test and a self-regulated learning questionnaire, both of which had been tested for validity and reliability. Data were analyzed descriptively through the calculation of mean scores, percentages, and the categorization of students’ mathematical reasoning skills and levels of self-regulated learning. The results showed that: 1) students with high self-regulated learning had high mathematical reasoning skills, with an average score of 70.50; 2) students with moderate self-regulated learning had moderate mathematical reasoning skills, with an average score of 43.67; and 3) students with low self-regulated learning had low mathematical reasoning skills, with an average score of 22.50. Thus, it can be concluded that the higher the students’ level of self-regulated learning, the better their mathematical reasoning skills.